Why railways fail: Colonial railways and economic development in Habsburg Bosnia–Herzegovina - Magnus Neubert; Stefan Nikolić (Journal of Development Economics, 2026)
Are railways always a harbinger of prosperity? We examine the economic effects of railways in Bosnia–Herzegovina under Habsburg colonial rule. Our novel dataset consistently tracks the non-agricultural population share of over 4500 settlements in Habsburg Bosnia in 1885, 1895, and 1910, based on census records. Applying the inconsequential units approach, with least-cost paths as our instrumental variable, we estimate the effect of railway access on occupational change. In settlements directly connected to imperial railways and competition, non-agricultural activity declined as craftsmen returned to agriculture. By contrast, the new railway network temporarily accelerated non-agricultural activity, primarily by attracting factories and foreign labor. Railway access generated more sustained non-agricultural employment growth in settlements with higher human capital and stronger law enforcement. Overall, our findings suggest that colonial railways did not uniformly promote economic development: while railway access reshaped local occupational structures, lasting positive effects depended on local development preconditions.
Keywords: I25; J21; N94; O18; R11; 330; railways; occupational structure; Bosnia-Herzegovina; Habsburg Empire